2014
DOI: 10.2174/1874213001407010009
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore Dynamics and Range Contraction in Kajiado County Kenya: Climate and Land Use Changes, Population Pressures, Governance, Policy and Human-wildlife Conflicts

Abstract: Wildlife populations are declining severely in many protected areas and unprotected pastoral areas of Africa. Rapid large-scale land use changes, poaching, climate change, rising population pressures, governance, policy, economic and socio-cultural transformations and competition with livestock all contribute to the declines in abundance. Here we analyze the population dynamics of 15 wildlife and four livestock species monitored using aerial surveys from 1977 to 2011 within Kajiado County of Kenya, with a rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 98 publications
(133 reference statements)
3
85
1
Order By: Relevance
“…The animal declines are mostly related to illegal hunting, land use changes, droughts, and isolation of protected areas through fencing [18][19][20]. However, trophy hunting promotes off-takes of a supposedly small proportion of males from a population [21] and the associated impacts on population dynamics of most polygamous ungulates are expected to be minimal [22].…”
Section: Introductionmentioning
confidence: 99%
“…The animal declines are mostly related to illegal hunting, land use changes, droughts, and isolation of protected areas through fencing [18][19][20]. However, trophy hunting promotes off-takes of a supposedly small proportion of males from a population [21] and the associated impacts on population dynamics of most polygamous ungulates are expected to be minimal [22].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we used the Regional Climate Models (RCM) with a better data that of the waterbuck and Thomson's gazelle had been declining continuously before the drought and it dropped distressingly to very low levels after the drought [23]. The impact of migratory species was high and the impacts on wildebeest as projected will be extremely severe.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that elephant population have also increased persistently in Kajiado east from 2000 to 2011 [23] [24] [37]. Therefore despite the increase in temperatures the elephant range is not threatened mainly because they are found in the Amboseli region which is relatively low temperature and has many swamps that guarantee their…”
Section: Discussionmentioning
confidence: 99%
“…African buffalo typically experience considerable droughtrelated mortality (Walker et al 1987;Ogutu and Owen-Smith 2003;Ryan et al 2007;Ogutu et al 2014). The effects of drought are most strongly felt when animal populations experience extreme food limitation and either engage in limited movements or occupy habitats that experience droughtrelated food limitation at some stage on their migration -like the Mara-Serengeti wildebeest.…”
Section: Discussionmentioning
confidence: 99%